Efficacy of Persian medicine herbal formulations (capsules and decoction) compared to standard care in patients with COVID‐19, a multicenter open‐labeled, randomized, controlled clinical trial. (4th October 2021) - Karimi, Mehrdad; Zarei, Azadeh; Soleymani, Samaneh; Jamalimoghadamsiahkali, Saeidreza; Asadi, Asmaa; Shati, Mohsen; Jafari, Mohieddin; Rezadoost, Hassan; Kordafshar, Gholamreza; Naghizadeh, Ayeh; Mardi, Raefeh; Namiranian, Parva; et al.
Abstract : Persian medicine has recommended clinical experiences and proper herbal remedies for prevention and treatment of microbial infections and respiratory diseases. An open‐label, randomized, controlled, multicenter trial was conducted at five hospitals in Tehran and Isfahan provinces of Iran on 358 hospitalized adult patients. A total of 174 patients received standard care and 184 received herbal remedies (polyherbal decoction every 8 hr and two herbal capsules every 12 hr) plus standard care for 7 days. The primary clinical endpoint was the duration of hospital stay, and secondary outcomes were clinical improvement of symptoms based on self‐assessment questionnaire. Results demonstrated that these natural decoction and capsules treatment plus routine care significantly decreased duration of hospital dyspnea (3.291 day vs. 6.468 days), accelerated clinical improvement, and decreased symptoms such as dry cough, dyspnea, muscle pain, headache, fatigue, anorexia, chills, runny nose, sputum cough, and vertigo in the treatment group compared with standard‐care group. Significant effects of these polyherbal formulations on improving the symptoms of COVID‐19 could be incredibly promising for managing this pandemic with acceptable tolerability.